Teaching quantum particles in one and three-dimensional boxes (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The work was developed with the purpose of showing the difficulties of teachers and schools for the insertion of topics of modern and contemporary physics in high school and showing the importance of its use to adapt to the social reality. We present the theoretical development developed in the classroom, with appropriate tools to the accessible language, showing the aspects of energy and probability of the particle in a region configured for the work in question. After the theoretical treatment, operations were developed with virtual experiment so that the students perceive in a visual way, the descriptions of the equations proposed to solve the determined functions. We analyze procedures and discuss the results. Finally, we consolidated the belief in the use of alternative methods in the classroom, showing the motivation of the students for the introduction of the theme, where they had initial contact of quantum mechanics, although we once developed topics of the old quantum mechanics, such as Heisenberg's uncertainty principle, Planck's constant, photoelectric effect, and Bohr's atom.